The Relationship between Knowledge and Attitudes in the Use of PPE by Mosaic Craftsman - Dharmayanti, Cokorda Istri; Negara, Ni Luh Gede Aris Maytadewi; Suparwati, Komang Tri Adi; Marniati, Marniati (Indonesian Journal of Global Health Research, 2023)
In the mosaic craftsmen it was found that the craftsmen did not use the correct PPE. The study aims to determine the relationship between knowledge and attitudes in using PPE on the level of work safety in mosaic makers in the Tegallalang sub-district, Bali. This study intends to provide input and information to craftsmen about the Personal Protective Equipment needed when working so that craftsmen are protected. This research is a type of analytic survey research. Based on the tabulation results of 13 mosaic makers who had a low level of knowledge about PPE, 12 people or 66.7% of them did not use complete PPE, 1 person or 14.3% of them wore or used complete PPE. As many as 6 mosaic craftsmen who have sufficient level of knowledge, 5 people or 27.8% of them use incomplete PPE, 1 person or 14% use complete PPE. Meanwhile, 6 mosaic makers who had a good level of knowledge included 1 person or 5.6% using incomplete PPE, 5 using complete PPE. Based on the results of the tabulation, it was found that 15 craftsmen had a negative attitude towards using PPE, 12 people or 66.7% of them did not use complete PPE, 3 of them or 42.9% of them used complete PPE. There were 10 craftsmen who had a positive attitude towards using PPE, 6 people or 33.3% of them did not use complete PPE, 4 people 57.1% used complete PPE. Based on the results of this study, it can be concluded that there is a relationship between knowledge and attitudes with the use of personal protective equipment for mosaic makers in the Tegalalang sub-district, the results obtained that there is a relationship between knowledge and attitudes in using PPE on the level of work safety in mosaic makers in the Tegallalang sub-district, Bali with p-value = 0.002 but there is no relationship on attitudes with p-value = 0.378 (ρ value <0.05).